The Dybbuk Century The Jewish Play That Possessed the World - Caplan, Debra; Moss, Rachel (University of Michigan Press, 2023)
A little over 100 years ago, the first production of An-sky's The Dybbuk, a play about the possession of a young woman by a dislocated spirit, opened in Warsaw. In the century that followed, The Dybbuk became a theatrical conduit for a wide range of discourses about Jews, belonging, and modernity. This timeless Yiddish play about spiritual possession beyond the grave would go on to exert a remarkable and unforgettable impact on modern theater, film, literature, music, and culture. The Dybbuk Century collects essays from an interdisciplinary group of scholars who explore the play's original Yiddish and Hebrew productions and offer critical reflections on the play's enduring influence. The collection will appeal to scholars, students, and theater practitioners, as well as general readers.